Sistem Pendukung Keputusan Pemilihan Mall Terbaik di Kota Pematangsiantar (Irian Mall, Suzuya Mall, Ramayana Mall) Dengan Metode Fuzzy Mamdani - Syafwan, Chalik; Simanjuntak, Apriando; Dyla Tri Aulia; Sinurat, Michael Sergio Vernandez; Sundari Retno Andani ((JRSIKOM) Jurnal Riset Sistem Informasi dan Aplikasi Komputer, 2025)
This research proposes a decision support system for selecting the best mall in Pematangsiantar City, employing the Mamdani fuzzy method. The four main selection criteria are location and accessibility, facilities, comfort, and visitor crowds. Each criterion is converted into a fuzzy membership degree using a triangular function with a predetermined range of values. The inference process uses IF-THEN rules, and defuzzification uses the centroid method. The evaluation results show that Suzuya Mall received a score of 90 (very feasible), while Irian Mall and Ramayana Mall received scores of 60 (feasible). This study demonstrates that Mamdani-based fuzzy systems can process qualitative and quantitative data to produce objective, easy-to-understand decision values.